Development, psychometric assessment, and predictive validity of a breastfeeding subjective norms scale among an Australian prospective cohort of first-time parents - Charlesworth, J.; McAlpine, T.; Martin, A.; Scott, Jane; Mullan, Barbara (WILEY, 2023)
Objectives: Breastfeeding has a number of benefits for both mothers and their infants. Research has examined the psychosocial influences on breastfeeding, yielding important findings in relation to particular constructs that play a significant role in this vital health behaviour. One such construct is subjective norms. However, there are mixed findings in relation to the role of subjective norms in breastfeeding behaviours. This may be due to the lack of consistent measure of subjective norms across studies. Further, the influence of fathers' subjective norms on breastfeeding continuation remains unclear due to a lack of measurement. Thus, the aim of the current study was to develop and assess a reliable and valid subjective norms scale specific to breastfeeding for use among both mothers and fathers. Design/Methods: Subjective norms items were developed by researchers in the domain and were tested among 949 couples. Results: Findings indicated that both subjective norms scales had excellent reliability, construct validity, and predictive validity. It was also found that both the mothers' and fathers' subjective norms scales tapped into two key structures: breastfeeding in general, and breastfeeding in public. Further, maternal subjective norms were predictive of breastfeeding behaviours but not paternal subjective norms. Conclusions: These findings indicate that the developed subjective norms scales are reliable and valid and capture key elements of breastfeeding subjective norms among both mothers and fathers. Use of this measure in future research can help better understand the role of both mothers' and fathers' subjective norms in influencing breastfeeding behaviours.